SASTERA MODEN MALAYSIA : Sebuah Pengenalan - Muhammad Haji Salleh (Institut Terjemahan & Buku Malaysia, 2023)
This book traces the development of Malaysian literature, from the last decade of the 18th century when Europeans invaded the Malay World